Development of Gayo language teaching materials as local content for fifth grade elementary school students - Hayati, Atia Uminda; Yusuf, Yusri; Alamsyah, Teuku (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
The Gayo language as a local content subject in various elementary schools in Central Aceh Regency has not been implemented optimally due to the lack of well-structured teaching materials that align with students' developmental backgrounds. This condition has led to low student motivation and limited schools' role as centers for preserving regional languages. This study aims to develop Gayo language teaching materials as local content learning resources for fifth-grade elementary school students in Central Aceh Regency. The approach used in this research is Research and Development (R&D), employing the Dick and Carey model, which consists of three main stages: needs analysis, design and development, and final evaluation and implementation. Data collection was carried out through interviews, observations, documentation, and questionnaires, both expert- and user-assessed. The research subjects involved teachers and fifth-grade students from five elementary schools in Central Aceh Regency. The novelty of this research lies in the development of Gayo language teaching materials that systematically integrate four language skills with local wisdom and are designed according to the contextual needs of elementary school students in Central Aceh Regency. The results show that the developed teaching materials are considered highly feasible by experts and users, and demonstrate strong effectiveness during the learning process. These materials can increase student motivation, assist teachers in organizing instruction, and strengthen local cultural identity.